L’éducation entrepreneuriale au primaire et au secondaire : gros plan sur la micro-entreprise scolaire - Pepin, Matthias (Canadian Journal of Education/Revue canadienne de l’éducation, 2011)
The student mini-company is the most emblematic pedagogical practice associated with the entrepreneurial education trend. This article demonstrates that if invariants constitute the ideas that are basic to the student mini-company, its organization may fluctuate, but also otherwise be based on different conceptions of entrepreneurship. To this effect, its contribution to students’ learning may take on many meanings. This report on an ethnographic inquiry process conducted within a micro-pulp mill, at the elementary school level, will serve as an occasion to question ourselves about different aspects concerning the student mini-company that deserve to be discussed. Key words: enterprise education; mini-company (mini-enterprise); K-12; educational ethnography; Canada (Québec).